Equality as a cooperative value and its projection in cooperative legislation - Macías Ruano, Antonio José (REVESCO. Revista de Estudios Cooperativos, 2022)
In the search for cooperative identity, the International Cooperative Alliance, on the basis of the elements that have been considered as identifying this legal structure, has established the principles and values of these entities, which are of a universal nature, to be accommodated as programmatic norms that guide the action and structure of cooperatives. And the cooperative principles being the "guidelines by which cooperatives put their values into practice" (ICA, 1995), analysing their legal materialization, cooperatives shall be distinguished from any other economic operator competing in the market. This paper aims to give an overview of the projection that one of the cooperative values has had in national legislative policy in the corporate sphere: equality. If values really are what sets cooperatives apart from other legal structures, the recognition of the value of equality in the legislative framework will give us a picture of the level of identification of the cooperative model in the market.
Keywords: Cooperative values; Equality; Gender equality; Societies; Cooperative societies; Capitalist societies; Cooperative identity; Laws